Deskripsi Ketersediaan Dan Pemanfaatan Media Pembelajaran Tematik Kelas V Sekolah Dasar Islam Al-Azhar 21 Pontianak Tenggara - Nurloviana Nurloviana; Siti Halidjah; Dyoty Auliya Vilda Ghasya (Departement of Mathematics Education, 2023)
This study aims to describe the availability and utilization of thematic learning media for class V Islamic Elementary School Al-Azhar 21 Pontianak Tenggara. The research method used is descriptive qualitative type. The participants in this study were teachers and students of class Va and Vb. Data collection techniques using observation techniques, interviews and documentation. The instruments used were checklist sheets, observation sheets, interview guidelines and documentation. The data analysis technique used is the Miles and Huberman model which includes four stages, namely data collection, data reduction, data presentation, and verification. The results showed that the availability of thematic learning media in Va and Vb classes, namely LCD, computers, pictures, posters, Bupena books, globes, atlases and maps. Not all existing media are used in the learning process, the use of media adapts to the subject matter. The learning media used by the teacher in the learning process are LCD, PowerPoint, pictures, posters, plasticine, YouTube videos, concrete media such as water, salt, sand, flour, milk, tea and coffee are also used in the learning process, especially in experimental activities. It can be concluded that the use of appropriate media in the learning process can generate motivation and enthusiasm for student learning in students.